Modulation of radiant oncological therapy through the intervention with substances of vegetable origin - Soledad Banega; Cintia Bertoncini; Mercedes Pascuccio; Alba Güerci (Brazilian Journal of Radiation Sciences, 2023)
Introduction: the search for substances that modulate the adverse effects of radiotherapy is key to optimizing the efficacy of these treatments and improving the patient's quality of life. We consider the evaluation of green tea (Camellia Sinensis) opportune for its antioxidant and anti-inflammatory properties, while its composition in polyphenols would make it possible to reduce radiosensitivity and improve cell recovery. Thus, our objective was to assess the efficacy of this infusion in the management of mucositis developed during radiant treatment of patients with head and neck cancer. Materials and Methods: a prospective and controlled clinical trial was carried out on a population of 20 patients, under treatment with intensity modulated radiation (IMRT). The result of the intervention with green tea rinses (4 times/day) or compliance with the usual protocol, was assessed by detailed recording of radiotoxicity, using the RTOG scale. Statistical analysis was performed using the T-Test: Student's t-Mann-Whitney U. Results: all the patients who adhered to and exhaustively complied with the protocol with the infusion, although they did not significantly recover the state of the oral cavity, demonstrated better control of the radio-induced acute effects (xerostomia and mucositis). Conclusion: although our results are preliminary, they allow us to suggest that from the intervention with green tea, the acute radiation-induced effects could be modulated. We believe intervention with this substance is opportune, given its easy administration, availability, cost, and lack of toxicity in a wide range of doses.